Filamentary high-resolution electrical probes for nanoengineering - Soh, EJH; Sarwat, GS; Mazzotta, G; Porter, BF; Riede, M; Nicholas, R; Kim, JS; Bhaskaran, H (American Chemical Society, 2020)
Confining electric fields to a nanoscale region is challenging yet crucial for applications such as high resolution probing of electrical properties of materials and electric-field manipulation of nanoparticles. State-of-the-art techniques involving atomic force microscopy typically have a lateral resolution limit of tens of nanometers due to limitations in the probe geometry and stray electric fields that extend over space. Engineering the probes is the most direct approach to improving this resolution limit. However, current methods to fabricate high-resolution probes, which can effectively confine the electric fields laterally involve expensive and sophisticated probe manipulation, which has limited the use of this approach. Here, we demonstrate that nanoscale phase switching of configurable thin films on probes can result in high-resolution electrical probes. These configurable coatings can be both germanium-antimony-tellurium (GST) as well as amorphous-carbon, materials known to undergo electric field-induced non-volatile, yet reversible switching. By forming a localized conductive filament through phase transition, we demonstrate a spatial resolution of electrical field beyond the geometrical limitations of commercial platinum probes (i.e. an improvement of ~48%). We then utilize these confined electric fields to manipulate nanoparticles with single nanoparticle precision via dielectrophoresis. Our results advance the field of nanomanufacturing and metrology with direct applications for pick and place assembly at the nanoscale.